Um anel romano de Stª Cristina dos Longos - Cravinho, Graça; Sousa, J. J. Rigaud de (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
It’s our purpose to describe, classify and date this roman ring and make the iconographic and symbolic study of the engraved motif on the gem set on it.